The Tacit Dimension - Polanyi, Michael 1891-1976 (Chicago, IL University of Chicago Press, 2009)
I shall reconsider human knowledge by starting from the fact that we can know more than we can tell, writes Michael Polanyi, whose work paved the way for the likes of Thomas Kuhn and Karl Popper. The Tacit Dimension argues that tacit knowledgetradition, inherited practices, implied values, and prejudgmentsis a crucial part of scientific knowledge. Back in print for a new generation of students and scholars, this volume challenges the assumption that skepticism, rather than established belief, lies at the heart of scientific discovery.
Keywords: 20th Century (1901-2000); Philosophy